Studi Komparasi Sektor E-commerce pada Awal dan Akhir Pandemi Covid-19 - Radias Kartika Utami; Muhammad Akmal Perdana; Tazkiratul Hamda; Siti Rahmah; Dewi Anggraini; Selvi Annisa (Jurnal Kajian Ilmiah, 2025)
This study examines the impact of the COVID-19 pandemic on the e-commerce sector in Indonesia by comparing its growth at the beginning and end of the pandemic. COVID-19 was first detected in Wuhan, China in December 2019 and became a global pandemic in March 2020. The pandemic affected various sectors, including the economy and business, with some sectors like e-commerce experiencing growth. This study uses a quantitative method with secondary data from "E-commerce Statistics 2020" and "E-commerce Statistics 2022" published by BPS. Data shows a significant increase in the number of e-commerce businesses, from 2,361,423 in 2020 to 2,995,986 in 2022. Correlation analysis and t-tests indicate a strong positive relationship and a significant difference in the number of e-commerce businesses between these periods. This study provides insights into the development of the e-commerce sector during the pandemic and aids stakeholders in making decisions in the post-pandemic era.